Genetic variants of SULT1A1 and XRCC1 genes and risk of lung cancer in Bangladeshi population. Issue 11 (October 2017) - Tasnim, Tasnova; Al-Mamun, Mir Md Abdullah; Nahid, Noor Ahmed; Islam, Md Reazul; Apu, Mohd Nazmul Hasan; Bushra, Most Umme; Rabbi, Sikder Nahidul Islam; Nahar, Zabun; Chowdhury, Jakir Ahmed; Ahmed, Maizbha Uddin; Islam, Mohammad Safiqul; Hasnat, Abul
Lung cancer is one of the most frequently occurring cancers throughout the world as well as in Bangladesh. This study aimed to correlate the prognostic and/or predictive value of functional polymorphisms in SULT1A1 (rs9282861) and XRCC1 (rs25487) genes and lung cancer risk in Bangladeshi population. A case-control study was conducted which comprises 202 lung cancer patients and 242 healthy volunteers taking into account the age, sex, and smoking status. After isolation of genomic DNA, genotyping was done by polymerase chain reaction–restriction fragment length polymorphism method and the lung cancer risk was evaluated as odds ratio that was adjusted for age, sex, and smoking status. A significant association was found between SULT1A1 rs9282861 and XRCC1 rs25487 polymorphisms and lung cancer risk. In case of rs9282861 polymorphism, Arg/His (adjusted odds ratio = 5.06, 95% confidence interval = 3.05–8.41, p < 0.05) and His/His (adjusted odds ratio = 3.88, 95% confidence interval = 2.20–6.82, p < 0.05) genotypes were strongly associated with increased risk of lung cancer in comparison to the Arg/Arg genotype. In case of rs25487 polymorphism, Arg/Gln heterozygote (adjusted odds ratio = 4.57, 95% confidence interval = 2.79–7.46, p < 0.05) and Gln/Gln mutant homozygote (adjusted odds ratio = 4.99, 95% confidence interval = 2.66–9.36, p < 0.05) were also found to be significantly associated with increased risk of lung cancer. This study demonstrates that the presence of His allele and Gln allele in case of SULT1A1 rs9282861 and XRCC1 rs25487, respectively, involve in lung cancer prognosis in Bangladeshi population.